Evaluation de nouvelles varieties digname en Cote dIvoire: bilan de trois annees dexperience avec des genotypes ameliores par lIITA - Ettien, J.B.; Tschannen, A.B. (2003)
Assessment of new yam varieties in Côte d'Ivoire : results of three experiments years with improved genotypes by IITA The most important food crop in the Ivory Coast, yam, is cultivated in a traditional system with low productivity. In order to suffice the needs of the growing population the introduction of new technologies increasing the production of yam is mandatory. One way suggested here is the introduction of new improved varieties. The aim of this project was to identify promising varieties which are resistant to the major diseases, offer high yields and an acceptable culinary quality. Trials have been conducted in Toumodi in the transition zone between savannah and forest in the Ivory Coast. The clones tested have been selected by the IITA in Nigeria. The trials were run from 1999 to 2001 and 46 clones of Dioscorea cayenensis-rotundata and 16 of D. alata were evaluated in a experimental setup called "augmented design". The yields in 1999 varied between 12 and 15 t/ha for D. alata (6 clones) and between 7 and 11.5 t/ha for D. cayenensis-rotundata (5 clones). In 2000 and 2001 higher yields were obtained: 7 to 20 t/ha among the 16 clones of D. alata and 7 – 23.5 t/ha among the 46 clones of D. cayenensis-rotundata. Both in 1999 all clones and species were evaluated sensorially. In 2000 only the quality control of the ten highest yielding clones of D. cayenensis-rotundata was carried out. These trials have permitted to select five promising clones whose culinary characteristics are close to local cultivars.